NIMA-related kinase 9 regulates the phosphorylation of the essential myosin light chain in the heart - Müller, Marion; Eghbalian, Rose; Boeckel, Jes-Niels; Frese, Karen S.; Haas, Jan; Kayvanpour, Elham; Sedaghat-Hamedani, Farbod; Lackner, Maximilian K.; Tugrul, Oguz Firat; Ruppert, Thomas; Tappu, Rewati; Martins Bordalo, Diana; et al. (Nature Communications, 2022)
To adapt to changing hemodynamic demands, regulatory mechanisms modulate actin-myosin-kinetics by calcium-dependent and -independent mechanisms. We investigate the posttranslational modification of human essential myosin light chain (ELC) and identify NIMA-related kinase 9 (NEK9) to interact with ELC. NEK9 is highly expressed in the heart and the interaction with ELC is calcium-dependent. Silencing of NEK9 results in blunting of calcium-dependent ELC-phosphorylation. CRISPR/Cas9-mediated disruption of NEK9 leads to cardiomyopathy in zebrafish. Binding to ELC is mediated via the protein kinase domain of NEK9. A causal relationship between NEK9 activity and ELC-phosphorylation is demonstrated by genetic sensitizing in-vivo. Finally, we observe significantly upregulated ELC-phosphorylation in dilated cardiomyopathy patients and provide a unique map of human ELC-phosphorylation-sites. In summary, NEK9-mediated ELC-phosphorylation is a calcium-dependent regulatory system mediating cardiac contraction and inotropy.